Autotransplantation and Orthodontic Treatment after Maxillary Central Incisor Region Trauma: A 13-Year Follow-Up Case Report Study - Farzad Piroozmand; Hossein Hessari; Mohsen Shirazi; Pegah Khazaei (Hindawi Limited, 2018)
The anterior maxilla is the most prone region to the trauma during childhood, and tooth loss sometimes happens due to trauma. Replacing the missing teeth has always been one of the dentists' challenges in children and adolescents, since their dentofacial growth is not complete. Autotransplantation of mandibular premolars with two-thirds or three-quarters of root formation provides the best prognosis for the tooth survival. This case report describes the management of a 10-year-old boy suffering a severe dental injury who received the autotransplantation of the premolars from mandible to restore the space caused by trauma in maxillary central incisor region and a 13-year follow-up of the autotransplantation.